Financial Performance Analysis at Aavas Financiers Ltd. - Shah, Maahir (ATLAS SkillTech University, 2024)
This includes an overview of the Sumer Internship Report conducted at Aavas Financiers Ltd. The main objective of working at this industry was to obtain practical experience and to gain knowledge and insights about the finance industry. During my time at Aavas Financiers Ltd, a comprehensive analysis was conducted including various aspects of the business, the process and procedure of how a finance and treasury department of an industry works and also their day to day tasks. Potential benefits and opportunities interning at Aavas Financiers Ltd.
Project Report on Financial Performance Analysis at Aavas Financiers Ltd. (2022-24) Under the Guidance of Prof. Apurva Mehta